Architecture for multicasting using private tunnel - Sidhu, Amandeep Singh (My University, 2013)
Multicast IP is a routing scheme for efficient streaming of media and other content over a network to selected host. By multiplication of the data in the routers on the way to their destination, it allows servers to save bandwidth by only sending one stream to multiple receivers. Using IP multicast techniques to distribute this information can often substantially reduce the overall bandwidth demands on the network. A good example of this approach is the rapidly growing area of audio and video Web content. The use of multicast over the internet is rather limited as most of the ISP router does not support Multicasting for lack of hardware support. In this thesis multicast will be explained and a simple method of sending multicast data over internet to other networks.
Master of Engineering (Software Engineering)
Keywords: Multicasting , Private Tunnel